A Syntactic—Stylistic Critique of Interjections & Ideophones with Reference to the IsiZulu Novel - Sizwe Zwelakhe Dlamini (Forum for Linguistic Studies, 2024)
Through the lenses of descriptive linguistics, interjections and ideophones are usually analysed separately from literature in the South African indigenous languages. Nothing much has been done so far to investigate these aspects through descriptive linguistics in context to literature. By investigating the syntactic features of interjections and ideophones, with reference to the IsiZulu novel genre, this paper seeks to harmonise literary criticism and linguistics. This study is theoretically and broadly grounded on linguistic stylistics, and it adopts Ngara’s linguistic proper format as the main theoretical base. With the analysis of four novels namely, Kungasa Ngifile, Ngidedele Ngife, Ngiyolibala Ngifile, and Inkululeko Engakhululekile, as primary sources, the study is done qualitatively through textual analysis. The findings of the study demonstrate that literary criticism and linguistics can co-exist even with reference to the isiZulu language as a case study. While interjections are discussed under the syntactic properties of them as complete sentences and auxiliaries in sentences, ideophones are discussed under the following sub – headings: Ideophones used with finite verbs, ideophones used with the verb stem -thi, and ideophones used independently. It is through these syntactic properties that the artistic or stylistic significance of interjections and ideophones in the novels are also demonstrated. Such an approach covers both the form (linguistic description) and function (literary significance) of interjections and ideophones.